Prominence of ileal mucosa-associated microbiota to predict postoperative endoscopic recurrence in Crohn’s disease - Sokol, Harry; Brot, Loic; Stefanescu, Carmen; Auzolle, Claire; Barnich, Nicolas; Buisson, Anthony; Fumery, Mathurin; Pariente, Benjamin; Le Bourhis, Lionel; Treton, Xavier; Nancey, Stéphane; Allez, Matthieu; et al. (Gut, 2020)
ObjectiveFollowing ileal resection for Crohn’s disease (CD), recurrence is very frequent. Although several clinical risk factors of recurrence have been identified, predicting relapse remains challenging. Performing an ileocolonoscopy within the first year after surgery is currently recommended to assess endoscopic recurrence and to adjust the treatment. We took advantage of a large prospective multicentric cohort to investigate the role of the ileal mucosa-associated microbiota in postoperative endoscopic recurrence.Patients and methodsIleal mucosa-associated microbiota was analysed by 16S sequencing at the time of surgery and/or of endoscopic evaluation in 201 patients (288 samples in total) prospectively recruited in France.ResultsIleal mucosa-associated microbiota exhibits profound changes following surgery in CD. Compared with non-recurrence setting, endoscopic recurrence is associated with strong changes in ileal mucosa-associated microbiota that are highly reminiscent of those observed generally in ileal CD compared with healthy subjects with a reduction in alpha diversity, an increase in several members of the Proteobacteria phylum and a decrease in several members of the Lachnospiraceae and the Ruminococcaceae families within the Firmicutes phylum. At the time of surgery, we identified several bacterial taxa associated with endoscopic recurrence and that can better predict relapse than usual clinical risk factors.ConclusionSurgery has an important impact on ileal mucosa-associated microbiota. Postoperative endoscopic recurrence is associated with changes in microbiota composition and alpha diversity. The gut microbiota has the potential to predict postoperative evolution and recurrence.